Efficient biosynthesis of (R)-2-chloro-1-(2, 4-dichlorophenyl) ethanol using a mutant short-chain dehydrogenase from Novosphingobium aromaticivorans. Issue 22 (28th May 2020) - Zhou, Yafeng; Zhao, Qiaojun; Zhou, Shuyao; Que, Fandi; Li, Guifang; Tang, Yunping
Graphical abstract: Highlights: A mutant Na SDR-G145A/I199L was used to produce antifungal drugs intermediate. The mechanism of increased enzyme activity was illustrated by molecular docking. 120 g/L substrate was reduced in 6 h with the conversion rate of 99%. The reaction was catalyzed by this mutant with an enantiomeric excess of 99.95%. Abstract: ( R )-2-chloro-1-(2, 4-dichlorophenyl) ethanol (( R )-CPEO) is an important chiral intermediate for antifungal drug synthesis. ( R )-CPEO can be produced from 2-chloro-1-(2, 4-dichlorophenyl) ethanone (CPE) via a mutant short-chain dehydrogenase/reductase from Novosphingobium aromaticivorans ( Na SDR). The Vmax of a mutant Na SDR-G145A/I199L toward CPE (6.32 U mg −1 ) was greater than that of wild-type Na SDR (2.58 U mg − ). The Km of mutant Na SDR-G145A/I199L toward CPE (0.23 mM) was less than that of wild-type Na SDR (0.38 mM), indicating that the substrate affinity of mutant Na SDR-G145A/I199L was the greater of the two. Docking simulations were used to illustrate the mechanisms of the increased enzyme activity of Na SDR-G145A/I199L; these showed that Na SDR-G145A/I199L presented a more effective docking posture than that of the wild-type enzyme. Further, Na SDR-G145A/I199L and glucose dehydrogenase (GDH) were used to transform 120 g/L CPE into ( R )-CPEO. After 6 h, the conversion rate and enantiomeric excess values were 99% and 99.95%, respectively. The present study provides a practical method for high substrate loading of ( R )-CPEO for industrial-scale applications.